TANGGUNG JAWAB HUKUM PERUSAHAAN ASURANSI TERHADAP PENGGUNA JASA ASURANSI ATAS KETIDAKBENARAN INFORMASI YANG DIBERIKAN (STUDI KASUS BPSK NOMOR PUTUSAN No. 001/A/BPSK DKI/1/2020) - Daffa Revizamardani, (2023)
Legal protection for consumers of insurance services regulated in the Consumer Protection Act, is a form of legal protection provided by the government to the public because of the increasing public interest in using insurance services, in addition to guaranteeing old age as well as to guard against future problems. However, the large number of people who do not understand how insurance services work and also the lack of information from insurance service providers to the public makes many legal problems occur between business actors providing insurance services and also people who do not understand insurance services, as an example in the research that will discussed below is the problem of incorrect information provided by the insurance company to users of insurance services. In this case, the user of the insurance service who was harmed chose to resolve the dispute at the Consumer Dispute Settlement Agency (BPSK). The type of research used in this journal is normative juridical research, namely research methods carried out by examining literature and secondary data only. In this writing, the writer uses a case approach technical writing. This approach is carried out by examining cases related to the legal issues at hand. The cases reviewed were cases with permanent legal force decided by the Consumer Dispute Settlement Agency (BPSK).